Highly stretchable strain sensors with improved sensitivity enabled by a hybrid of carbon nanotube and graphene - Leilei Wang; Jungwook Choi (Micro and Nano Systems Letters, 2022)
Abstract The development of high-performance strain sensors has attracted significant attention in the field of smart wearable devices. However, stretchable strain sensors usually suffer from a trade-off between sensitivity and sensing range. In this study, we investigate a highly sensitive and stretchable piezoresistive strain sensor composed of a hybrid film of 1D multi-walled carbon nanotube (MWCNT) and 2D graphene that forms a percolation network on Ecoflex substrate by spray coating. The mass of spray-coated MWCNT and graphene and their mass ratio are modulated to overcome the trade-off between strain sensitivity and sensing range. We experimentally found that a stable percolation network is formed by 0.18 mg of MWCNTs (coating area of 200 mm2), with a maximum gauge factor (GF) of 1,935.6 and stretchability of 814.2%. By incorporating the 0.36 mg of graphene into the MWCNT film (i.e., a mass ratio of 1:2 between MWCNT and graphene), the GF is further improved to 12,144.7 in a strain range of 650–700%. This high GF is caused by the easy separation of the graphene network under the applied strain due to its two-dimensional (2D) shape. High stretchability originates from the high aspect ratio of MWCNTs that bridges the randomly distributed graphenes, maintaining a conductive network even under sizeable tensile strain. Furthermore, a small difference in work function between MWCNT and graphene and their stable percolation network enables sensitive UV light detection even under a significant strain of 300% that cannot be achieved by sensors composed of MWCNT- or graphene-only. The hybrids of MWCNT and graphene provide an opportunity to achieve high-performance stretchable devices.